2021
DOI: 10.5194/se-2021-68
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detrital zircon provenance record of the Zagros mountain building from the Neotethys obduction to the Arabia-Eurasia collision, NW Zagros fold-thrust belt, Kurdistan region of Iraq

Abstract: Abstract. Recognition of new angular unconformity and synthesizing of new detrital zircon U-Pb and (U-Th)/He provenance records, including zircon (U-Th)/(He-Pb) double dating, from the NW Zagros elucidate the basin dynamics of the foreland wedge-top and intermontane units, as well as the tectonic processes in the source terranes in response to different geodynamic phases. In this contribution, we present field observations and detrital zircon provenance data from hinterland basins to reconstruct the basin dyna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The Merga I unit has variable thickness and locally disappeared along the Imbricated zone; Merga II is usually 200-250 m thick. Koshnaw et al (2021) confirmed the existence of Merag Red bed group around Mawat district. North to the Mawat district numerous numbers of exotic boulders of manganese ore have been recently observed associated probably with the Merga unit, varying in size from 10 cm to 2 m. They are very hard massive blocky with deep black color.…”
Section: The Intermontane Molasse Basin (Merga Red Beds Group)mentioning
confidence: 52%
See 1 more Smart Citation
“…The Merga I unit has variable thickness and locally disappeared along the Imbricated zone; Merga II is usually 200-250 m thick. Koshnaw et al (2021) confirmed the existence of Merag Red bed group around Mawat district. North to the Mawat district numerous numbers of exotic boulders of manganese ore have been recently observed associated probably with the Merga unit, varying in size from 10 cm to 2 m. They are very hard massive blocky with deep black color.…”
Section: The Intermontane Molasse Basin (Merga Red Beds Group)mentioning
confidence: 52%
“…The Zagros orogenic belts are tectonic response of prolonged cretaceous to the Paleogene subduction collision cycle between Arabian and Eurasian plates (Mohammad and Cornell, 2017). These plates amalgamation leading to coexist different geological and tectonic units treading NW-SE ranging from Precambrian to Paleogene (Koshnaw et al,2021). In the frame of the regional tectonic anatomy of Zagros orogenic belt (Gürbüz and Farzipour Saein, 2019), Zagros orogenic belt in the Kurdistan region of Iraq encompass three parallel NW-SE-trending tectonic units.…”
Section: Regional Geologymentioning
confidence: 99%